2017
DOI: 10.11648/j.ijmsa.20170603.17
|View full text |Cite
|
Sign up to set email alerts
|

Application and Development of Wavefront Sensor Technology

Abstract: Wavefront sensing technology can directly test the phase distribution of wavefront distortion and has the advantages of simple operation, real-time and large dynamic range. It is widely used in adaptive optics, laser beam quality diagnosis, laser atmospheric communication, optical element and optics system detection, quantitative phase microscope, human eye aberration measurement and other fields. This paper mainly elaborates application and development of wavefront sensing technology in different fields. Comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Carmen Canovas and Erez N. Ribak compared and analyzed SHWFS methods (convolution, interpolation, Fourier methods, and centroid methods) for ophthalmology, and found that the Fourier method has the best effect for pupils with a small slope of the boundary or with a large distance from the boundary [ 19 ]. In the field of optical detection, such as the surface shape detection of high-order parabolic mirrors and conventional optical elements, it is important to reduce the measurement error by overcoming the problem of steep or linear edges [ 20 , 21 , 22 , 23 , 24 ]. In addition, researchers are focused on trying to rectify the distortion caused by the atmosphere to the propagating laser beam, which may detect optical vortices [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carmen Canovas and Erez N. Ribak compared and analyzed SHWFS methods (convolution, interpolation, Fourier methods, and centroid methods) for ophthalmology, and found that the Fourier method has the best effect for pupils with a small slope of the boundary or with a large distance from the boundary [ 19 ]. In the field of optical detection, such as the surface shape detection of high-order parabolic mirrors and conventional optical elements, it is important to reduce the measurement error by overcoming the problem of steep or linear edges [ 20 , 21 , 22 , 23 , 24 ]. In addition, researchers are focused on trying to rectify the distortion caused by the atmosphere to the propagating laser beam, which may detect optical vortices [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%